WW and C2 domain–containing proteins regulate hepatic cell differentiation and tumorigenesis through the hippo signaling pathway. Issue 4 (18th February 2018) - Hermann, Anke; Wennmann, Dirk Oliver; Gromnitza, Sascha; Edeling, Maria; Van Marck, Veerle; Sudol, Marius; Schaefer, Liliana; Duning, Kerstin; Weide, Thomas; Pavenstädt, Hermann; Kremerskothen, Joachim
Abstract : The Hippo pathway regulates cell differentiation, proliferation, and apoptosis. Upon activation, it inhibits the import of the transcriptional coactivator yes‐associated protein (YAP) into the nucleus, thus suppressing transcription of pro‐proliferative genes. Hence, dynamic and precise control of the Hippo pathway is crucial for organ size control and the prevention of tumor formation. Hippo signaling is controlled by a growing number of upstream regulators, including WW and C2 domain–containing (WWC) proteins, which trigger a serine/threonine kinase pathway. One component of this is the large tumor suppressor (LATS) kinase, which phosphorylates YAP, trapping it in the cytoplasm. WWC proteins have been shown to interact with LATS in vitro and stimulate its kinase activity, thus directly promoting cytoplasmic accumulation of phosphorylated YAP. However, the function of the WWC proteins in the regulation of cell proliferation, organ size control, and tumor prevention in vivo has not yet been determined. Here, we show that loss of hepatic WWC expression in mice leads to tissue overgrowth, inflammation, fibrosis, and formation of liver carcinoma. WWC‐deficient mouse livers display reduced LATS activity, increased YAP‐mediated gene transcription, and enhanced proliferation of hepatic progenitor cells. In addition, loss of WWC expression in the liver accelerates the turnover of angiomotin proteins, which act as negative regulators of YAP activity. Conclusion : Our data define an essential in vivo function for WWC proteins as regulators of canonical and noncanonical Hippo signaling in hepatic cell growth and liver tumorigenesis. Thus, expression of WWC proteins may serve as novel prognostic factors in human liver carcinoma. (Hepatology 2018;67:1546‐1559)